Is your drinking-water safe? A rotavirus outbreak linked to water refilling stations in the Philippines, 2016 - Rebato, Nino Dacanay; de los Reyes, Vikki Carr; Sucaldito, Ma. Nemia; Marin, Gretchen (Western Pacific Surveillance and Response, 2019)
Introduction: In April 2016, the Department of Health in Zamboanga Peninsula reported an increase in the number of acute gastroenteritis cases reported from Zamboanga City. An epidemiologic investigation was conducted to verify the existence of an outbreak, determine source/mode of transmission and recommend control measures.Methods: A line list of cases was compiled from the 11 hospitals within Zamboanga City and a case-series study was conducted. Suspected cases were any persons from Zamboanga City who had three or more episodes of acute diarrhoea within 24 hours from 15 March to 29 May 2016. Confirmed cases were suspected cases with active symptoms during the investigation who had a stool sample collected with rotavirus detected. Water samples were also collected for viral detection.Results: There were 2936 suspected cases with 22 deaths (case fatality rate: 0.75%), an age range of 8 days to 89 years (median: 2 years), with those aged less than 5 years the most affected age group (1903/2936, 65%). The majority were males (1549/2936, 53%). From the 138 active case patients included in the case-series study, the majority reported contact with a family member who had diarrhoea (89/138, 64%) and using water refilling stations as their major source of drinking-water (88/134, 64%). Of the 93 stool specimens collected, 56 (60%) were positive for rotavirus. Five samples from water refilling stations where case patients reported collecting drinking-water were all positive for rotavirus.Discussion: Strict regulation of water refilling stations and boiling drinking-water in households were implemented, immediately controlling the outbreak. After complying with all the requirements set by the Department of Health, a water safety certificate was awarded to Zamboanga City in September 2018.